Perencanaan Strategis Sistem Informasi Sekolah Tinggi Agama Islam Negeri Pamekasan - Jawa timur - - STAIN Pamekasan, Nirwana Haidar Hari (Indonesian Journal of Networking and Security (IJNS), 2016)
Abstract - Each university has a business needs to be achieved. In achieving these business needs, the role of information technology in particular with regard to Information Systems become an important partner. However, in the fulfillment of the Information System in accordance with business requirements, required a strategic planning and can be reached in a short time.State Islamic High School Pamekasan (STAIN Pamekasan) is a university that wants to continue to Develop information systems that exist, so will be able to meet all the needs of businesses, particularly in the areas of service. With the development of information systems, the STAIN Pamekasan can compete with universities around which is considered to be competitors.The methodology used in the study of Information Systems Strategic Planning State Islamic High School Pamekasan using the methodology of Strategic Planning Information Technology Architecture developed by Prof. Richardus Eko Indrajit.The outcome of the research is to make the establishment of programs, projects, and map waveguide (roadmap) which covers an area of organization, technology infrastructure and applications making it easier for management to manage the resources required to produce the information, accurate and can be used by all parties.Keywords: strategic planning, information systems, information technology architecture, business needs, map waveguide; Abstrak – Setiap Perguruan Tinggi memiliki kebutuhan bisnis yang harus dicapai. Dalam pencapaian kebutuhan bisnis tersebut, peranan Teknologi Informasi khususnya yang berkaitan dengan Sistem Informasi menjadi sangan penting. Akan tetapi, dalam pemenuhan Sistem Informasi yang sesuai dengan kebutuhan bisnis, diperlukan sebuah perencanaan yang strategis dan ditempuh dalam waktu yang tidak singkat.Sekolah Tinggi Agama Islam Negeri Pamekasan (STAIN Pamekasan) merupakan perguruan tinggi yang ingin terus mengembangkan sistem informasi yang ada, agar nantinya dapat memenuhi segala kebutuhan bisnis khususnya di bidang pelayanan. Dengan dikembangkannya sistem informasi, STAIN Pamekasan dapat bersaing dengan perguruan tinggi sekitar yang dianggap menjadi kompetitor. Metodologi yang digunakan dalam penelitian Perencanaan Strategis Sistem Informasi Sekolah Tinggi Agama Islam Negeri Pamekasan menggunakan metodologi Perencanaan Strategis Arsitektur Teknologi Informasi yang dikembangkan oleh Prof. Richardus Eko Indrajit.Hasil yang dicapai dari penelitian adalah membuat penetapan program, proyek, dan peta pandu (roadmap) yang meliputi area organisasi, infrastruktur teknologi dan aplikasi sehingga memudahkan manajemen mengelola sumber daya untuk menghasilkan informasi yang dibutuhkan, akurat dan dapat digunakan oleh semua pihak.Kata kunci:  perencanaan strategis, sistem informasi, arsitektur teknologi informasi, kebutuhan bisnis, peta pandu;